Pengembangan dan Implementasi Sistem Informasi Penelitian dan Pengabdian kepada Masyarakat Berbasis Web di Universitas Asa Indonesia - Roby Darmadi; Yana Shintya; Gunawan Sibuea; Faizal Pasaribu; Junedi Hutagaol (Universitas Pahlawan Tuanku Tambusai, 2026)
The management of research and community service activities (Penelitian dan Pengabdian kepada Masyarakat/PPM) at Universitas Asa Indonesia (ASAINDO) has been conducted manually through email, Microsoft Word, and Microsoft Excel, resulting in administrative inefficiency, data fragmentation, and considerable difficulties in monitoring and reporting. This community service program aims to design, develop, and implement a web-based Research and Community Service Information System (SIMLITASA) as an integrated solution to address these challenges. A prototyping approach was employed, encompassing four sequential phases: system analysis and design, system development, implementation and training, and monitoring and evaluation. SIMLITASA was developed using the PHP Laravel framework with a MySQL database and incorporates five core modules: online proposal submission, review management, monitoring dashboard, digital output repository, and automated reporting. The results of the PkM activities demonstrated that training participants were able to operate SIMLITASA independently. Implementation of this system is expected to improve the efficiency, transparency, and accountability of PPM governance at Universitas Asa Indonesia.